Переваги та недоліки існуючих форм управління ланцюгами поставок, як елемент визначення перспектив конкурентного розвитку підприємства - Антипенко, Є. Ю. (Ways to Improve Construction Efficiency, 2013)
The paper discusses and analyzes the existing organizational forms of business management and supply chain systems under current conditions and identified their strengths and weaknesses. The conclusion about the need for improvement in order to improve the competitive prospects of the company was done.